Transcription Analysis of the Stress and Immune Response Genes to Temperature Stress in Ostrinia furnacalis - Chen, Kangkang; Tang, Tai; Song, Qisheng; Wang, Zhenying; He, Kanglai; Liu, Xu; Song, Jiahui; Wang, Libao; Yang, Yizhong; Feng, Congjing (Frontiers in Physiology, 2019)
Ostrinia furnacalis is one of the most important pests on maize. O. furnacalis larvae are frequently exposed to the temperature challenges such as high temperature in summer and cold temperature in winter in the natural environment. High and low temperature stress, like any abiotic stress, impairs the physiology and development of insects. Up to now, there is limited information about gene regulation and signaling pathways related to the high and cold stress response in O. furnacalis. High-throughput sequencing of transcriptome provides a new approach for detecting stress and immune response genes under high and low temperature stresses in O. furnacalis. In the present study, O. furnacalis larvae were treated with the temperature at 8 °C and 40 °C, and the responses of O. furnacalis larvae to the temperature stress were investigated through RNA-sequencing and further confirmation. The results showed that immune responses were up-regulated in larvae by the cold stress at 8 °C while some stress response genes, such as HSP family, GST-2, Bax inhibitor and P450, were significantly increased at 40 °C. Furthermore, quantitative real time polymerase chain reaction were performed to quantify the expression levels of immune related genes, such as PGRP-LB, antimicrobial peptides, lysozyme, serine protease and stress response genes such as small HSPs and HSP90, and the expression levels of these genes were similar to the RNA-seq results. In addition, the iron storage protein Ferritin was found to be involved in the response to temperature stress, and the changes of total iron concentration in the hemolymph were, in general, consistent with the expression levels of Ferritin. Taken together, our results suggested that the stress response genes were involved in the defense against the heat stress at 40 °C, and the immune responses triggered by cold stress might provide protection for larvae from cold stress at 8 °C. More interestingly, our results showed that during the responses to temperature stress, the total iron concentration in hemolymph regulated by Ferritin increased, which might help O. furnacalis in surviving the low and high temperature stress.